Forgiveness, pardon and justice: Critical reflections on Eric Lomax's The Railway Man - Leah, Gordon (Theology, 2018)
This piece examines the famous event whereby Eric Lomax, author of The Railway Man, forgives the Japanese interpreter, Nagase, for his involvement in his torture in 1943. I consider the circumstances of the torture, Nagase's penitence and the protracted process of Lomax's forgiveness. I examine whether some acts are unforgivable, the difference between forgiveness and unconditional pardon, and how Christ through his expiatory death achieves the pardon that only he, as the Son of God, can achieve for his executioners and for all humanity. Thus, what might seem unforgivable is forgiven in Christ's name, through whom ultimate justice, if not restitution, is achieved.